Synthesis, Characterization, and Catalytic Properties of Magnetic Fe3O4@FU: A Heterogeneous Nanostructured Mesoporous Bio-Based Catalyst for the Synthesis of Imidazole Derivatives - Banazadeh, Maryam; Amirnejat, Sara; Javanshir, Shahrzad (Frontiers in Chemistry, 2020)
In this protocol, Fucoidan (FU), a fucose-rich sulfated polysaccharide extracted from brown algae Fucus vesiculosus was used for in situ preparation of magnetic Fe3O4@FU nanocomposites studied as an environmental bio-based heterogeneous catalyst. The structural and magnetic properties of Fe3O4@FU were investigated by energy dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Brunauer–Emmett–Teller ( BET) adsorption method, and vibrating sample magnetometer (VSM). The catalytic activity of Fe3O4@FU was employed for the synthesis of tri- and tetra-substituted imidazoles through a three- and four component reactions respectively between benzyl, aldehydes, NH4OAc and benzyl, aldehydes, NH4OAc and amine under reflux in ethanol. It is worth nothing that excellent yields, short reaction times, chromatography-free purification, environmentally friendly are highlighted features of this protocol.